(untitled) (Global Scientific Review, 2024)
The media serves many fundamental purposes in our society. Obviously, entertainment plays a part. The media has the power to ignite our imaginations, provide fantasy, and provide a means of escape. When discussing mass media, there are two main categories: broadcast media, which includes radio and television, and print media, which includes newspapers and magazines. While newspapers and magazines provided us with news during the 19th and early 20th centuries, electronic journalism—especially television journalism—has taken over in the last 50 years. The lines separating print and broadcast media are becoming increasingly hazy due to technological advancements. Information that is also broadcast on television and radio, as well as written in newspapers and periodicals, can be accessed over the Internet.